Peningkatan Kemampuan Digitalisasi Guru Sekolah Dasar dalam Pembuatan Media Pembelajaran Interaktif - Rosmalina, Rosma; Nistrina, Khilda Nistrina; Sukiman; Wulan Nurul Kamilah; Siti Dwi Rahayu (Komunikasi, 2024)
In the digital era, teachers are expected to utilize technology to create interactive learning media. However, many elementary school teachers still face limitations in mastering digital skills, including the use of software to develop engaging learning media. This is due to a lack of training, limited access to technology, and insufficient time to develop these skills. Consequently, the learning process becomes less engaging and less relevant to the current needs of students. The objectives of this research are to analyze the initial level of teachers' digitalization skills and their ability to create interactive learning media. To develop an effective training program to enhance teachers' digital skills. to evaluate the impact of the training on teachers' ability to create interactive learning media. to provide strategic recommendations for implementing similar training programs in other elementary schools. This study employs Classroom Action Research methods with a descriptive and quantitative approach. The findings include Initial Teacher Capability: Most teachers have a basic understanding of technology but lack practical application skills for creating interactive learning media. Training Effectiveness: The provided training significantly improved teachers' ability to use tools such as Canva and PowerPoint with engaging animations. Attitudinal Changes: Teachers became more confident in using technology for teaching and were more motivated to continuously develop their digital skills.